Combining inception-V3 and support vector machine for garbage classification - Intan Nurma Yulita; Firman Ardiansyah; Muhammad Rasyid Ramdhani; Mokhamad Arfan Wicaksono; Agus Trisanto; Asep Sholahuddin (JURNAL INFOTEL, 2023)
The global volume of trash has increased due to population growth and consumption, with a growing variety of materials and materials being generated. Inadequate garbage disposal practices, particularly in plastics, have led to environmental contamination and pollution in various regions. Artificial Intelligence (AI) technologies, particularly in machine learning, have demonstrated significant potential in trash sorting, particularly in the realm of machine learning. The Inception-V3 model and Support Vector Machines (SVM) are used in this study to extract relevant features and classify garbage categories. The Inception-V3 and SVM combination exhibits superior performance, with greater accuracy and F1 score compared to other methods. The radial basis function (RBF) kernel is the most optimal model of SVM, but it faces challenges in accurately categorizing the "trash" category due to limited data and resemblance to the "paper" class. The system developed in this study has a high level of effectiveness, with superior accuracy and F1 scores of 0.876 and 0.874, respectively.